A c / mo s2 alternate stack composite coating with excellent tribological properties and a method of making the same
Patent Information
- Application Number
- CN202610946506.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-10-09
AI Technical Summary
[0006]本发明的目的在于解决现有MoS2涂层承载性能不足、共溅射法结构调控精度差,以及含金属Ti多层涂层存在层间内应力、晶格失配、易剥落且无法抑制 MoS2柱状晶生长的技术问题,提供一种无金属掺杂、可精准调控堆叠顺序的C/ MoS2交替堆叠复合涂层及制备方法,依托碳层与二硫化钼层交替结构设计,消除界面结构缺陷,兼顾高承载能力与优异减摩耐磨性能
1. 揭示了协同增强机理:通过系统的结构设计和对比,明确了硬支撑层(C层)和低剪切层(MoS2层)的最优排布方式。
Smart Images

Figure CN122879646A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid lubricant coating preparation technology, specifically relating to a C / MoS2 alternating stacked composite coating with excellent tribological properties and its preparation method. Background Technology
[0002] Molybdenum disulfide (MoS2), a classic two-dimensional layered material, exhibits excellent friction-reducing and wear-resistant properties due to its ease of shear slip between layers. It is widely used in critical moving parts in aerospace, precision instruments, and other fields, especially under harsh conditions such as vacuum or inert atmospheres. However, a single MoS2 coating has low hardness and limited load-bearing capacity, making it prone to failure under high loads or harsh environments, thus limiting its application in a wider range of industrial sectors.
[0003] To overcome this deficiency, those skilled in the art generally employ a technique of introducing hard phases (such as metals, carbon, nitrides, etc.) into MoS2 to form composite coatings, aiming to significantly improve the hardness and load-bearing capacity of the coating while maintaining its low coefficient of friction. Currently, the mainstream preparation methods are mainly divided into two categories, but both have their own limitations: The first type is co-sputtering. This method involves simultaneously sputtering multiple targets (e.g., MoS2 and graphite targets) to allow different components to be mixed and deposited on the substrate surface, sometimes forming nanoscale self-assembled multilayer structures under specific process conditions. The drawback of this method is that the so-called "self-assembly" process is the result of the spontaneous interaction of various physicochemical factors during deposition, making it difficult to precisely and predictably control the thickness, composition, and interlayer interfaces of each functional layer (such as the hard layer and the lubricating layer). This uncertainty in control greatly limits the possibility of finely optimizing the coating structure to obtain the best synergistic enhancement effect, resulting in limited potential for performance improvement.
[0004] The second type is sequential sputtering, which involves time-sharing or alternating sputtering of different targets to deposit different materials layer by layer, thereby constructing a multilayer film with a clear structure. Compared to co-sputtering, this top-down construction method makes it possible to precisely control the thickness and interface of each layer. For example, invention application CN119243098B discloses an adaptive molybdenum disulfide-based multilayer composite film resistant to low-Earth orbit space irradiation and its preparation method. Through sequential sputtering, a multilayer structure is sequentially generated on the substrate, consisting of a Ti bonding layer, a MoS2-Ti gradient transition layer, a MoS2-Ti functional layer, a MoS2-Ti-C gradient transition layer, and a MoS2-C functional layer. The film-substrate adhesion and space irradiation resistance are improved by doping with metallic Ti. However, this structure introduces metallic Ti as the bonding layer, transition layer and doping phase throughout the process. The crystal structure, thermal expansion coefficient and elastic modulus of metallic Ti are very different from those of MoS2 / C. This easily leads to high internal stress, lattice mismatch and interface pores in the interlayer, causing the film-substrate bonding force to decay rapidly over time. This can easily result in local peeling and flaking. The coating density is interrupted by the metallic phase, making it impossible to form a continuous and dense protective structure. The gradient composition structure cannot stably suppress the growth of MoS2 columnar crystals.
[0005] Therefore, developing a method to control the internal structure of C / MoS2 multilayer composite coatings through precise and designable stacking order, eliminating metallic transition phases and gradient structures, fundamentally eliminating interfacial stress and lattice mismatch defects, and simultaneously achieving functional decoupling of strong load-bearing capacity at the bottom layer and excellent lubrication at the surface layer, in order to overcome the performance bottleneck of existing technologies, is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] The purpose of this invention is to solve the technical problems of insufficient load-bearing capacity of existing MoS2 coatings, poor structural control precision of co-sputtering method, and the existence of interlayer internal stress, lattice mismatch, easy peeling and inability to suppress the growth of MoS2 columnar crystals in multilayer coatings containing metallic Ti. The invention provides a metal-free C / MoS2 alternating stacked composite coating and its preparation method, which can precisely control the stacking order. Based on the alternating structure design of carbon layer and molybdenum disulfide layer, it eliminates interface structural defects and takes into account both high load-bearing capacity and excellent friction reduction and wear resistance.
[0007] The technical solution of the present invention is as follows: a C / MoS2 alternating stacked composite coating with excellent tribological properties, wherein the composite coating is attached to the surface of a substrate, and the composite coating is formed by alternating stacking of carbon layers and molybdenum disulfide layers. The innermost layer of the composite coating is a carbon layer in contact with the substrate, and the outermost layer is a molybdenum disulfide layer, and both the carbon layer and the molybdenum disulfide layer are at least one layer; the thickness of each carbon layer is 0.08~0.30 μm, and the thickness of each molybdenum disulfide layer is 0.12~0.45 μm; the total thickness of the composite coating is 0.56~0.8 μm.
[0008] Preferably, when both the carbon layer and the molybdenum disulfide layer are single layers, the thickness of the carbon layer is 0.2~0.3 μm and the thickness of the molybdenum disulfide layer is 0.36~0.45 μm.
[0009] Preferably, when both the carbon layer and the molybdenum disulfide layer are two layers, the thickness of each carbon layer is 0.12~0.18 μm and the thickness of each molybdenum disulfide layer is 0.17~0.22 μm.
[0010] Preferably, when both the carbon layer and the molybdenum disulfide layer are three layers, the thickness of each carbon layer is 0.08~0.1 μm and the thickness of each molybdenum disulfide layer is 0.12~0.14 μm.
[0011] Preferably, when both the carbon layer and the molybdenum disulfide layer are two layers, the thickness of each carbon layer is 0.15 μm and the thickness of each molybdenum disulfide layer is 0.21 μm.
[0012] Regarding coating thickness, if it is too thin (too short deposition time), it will be worn through by the mating system in a short period of time, losing its long-term lubrication. If it is too thick (too long deposition time), it will cause a surge in internal stress in the coating, making it prone to peeling and flaking, and reducing the adhesion between the film and the substrate.
[0013] The method for preparing the C / MoS2 alternating stacked composite coating with excellent tribological properties as described above includes the following steps: Step 1) After cleaning and drying the substrate, place it in the magnetron sputtering chamber and set the substrate temperature; Step 2) Under a protective atmosphere, according to the preset stacking cycle, number of stacked layers and design thickness of each single layer of the composite coating, set the deposition time of each layer by magnetron sputtering, and use graphite target and molybdenum disulfide target alternately for sputtering deposition. First, deposit a carbon layer on the substrate, and then deposit a molybdenum disulfide layer on the carbon layer. Repeat this alternating deposition cycle until the preset number of stacked layers of the composite coating is reached. Step 3) After deposition, cool to room temperature to obtain a C / MoS2 alternating stacked composite coating deposited on the substrate.
[0014] Preferably, in step 1), the substrate temperature is set to 180 °C.
[0015] Preferably, in step 2), the protective gas is argon, the gas flow rate is 20 sccm, and the gas pressure is 1.0 Pa.
[0016] Preferably, in step 2), the carbon layer is deposited using DC magnetron sputtering mode with a sputtering power of 120 W, a substrate bias of 80 V, and a total deposition time of 90 min for each carbon layer; the molybdenum disulfide layer is deposited using radio frequency magnetron sputtering mode with a sputtering power of 80 W and a total deposition time of 90 min for each molybdenum disulfide layer.
[0017] The application of the C / MoS2 alternating stacked composite coating with excellent tribological properties, as described above, in friction reduction and protection of critical moving parts of precision instruments.
[0018] The beneficial effects of this invention are as follows: 1. The synergistic enhancement mechanism was revealed: through the structural design and comparison of the system, the optimal arrangement of the hard support layer (C layer) and the low shear layer (MoS2 layer) was clarified.
[0019] 2. This coating possesses comprehensive properties including low friction, high wear resistance, and structural stability.
[0020] 3. The inner C layer serves as the foundation and framework for the overlapping coatings, which significantly enhances the overall hardness and compressive strength of the coating.
[0021] 4. The outermost MoS2 layer ensures that the system has an ideal friction-reducing surface.
[0022] 5. Simple process and good controllability: It adopts mature magnetron sputtering technology, and complex layered structure design can be achieved by simply adjusting the sputtering sequence of different target materials. The process has good repeatability and is easy to industrialize. Attached Figure Description
[0023] Figure 1 is a schematic diagram of the magnetron sputtering system of the present invention and a structural design diagram of the MoS2 / C alternating stacked composite coating; (a) is a schematic diagram of the magnetron sputtering preparation system used in this invention; (b) Design drawings of the coating structures obtained in Examples 1-2 and Comparative Examples 1-4; Figure 2 This is a schematic diagram of the ball-disc friction tester used to test the coefficient of friction of the coatings in the various embodiments and comparative examples; Figure 3 These are schematic diagrams showing the test results of the coating friction coefficients in various embodiments and comparative examples; wherein, (a) Curves showing the change of friction coefficient over time in each embodiment and comparative example during the test process; (b) is the average value of the friction coefficients of each embodiment and comparative example; Figure 4 The morphology of the wear region and the wear track cross-sectional depth profile curves of the coatings in each embodiment and comparative example are shown; wherein, (a) is a surface morphology of the wear marks on the coating of Comparative Example 1 (D1); (b) is a surface morphology diagram of the wear marks on the coating of Comparative Example 2 (D2); (c) is a surface morphology diagram of the wear marks on the coating of Example 1 (S1); (d) is a surface morphology diagram of the wear marks on the coating of Comparative Example 3 (D3); (e) is a surface morphology diagram of the wear marks on the coating of Comparative Example 4 (D4); (f) is a surface morphology diagram of the wear marks on the coating of Example 2 (S2); (g) is the wear track depth profile curve of the coating in Comparative Example 1 (D1); (h) is the wear track depth profile curve of the coating in Comparative Example 2 (D2); (i) is the wear track depth profile curve of the coating in Example 1 (S1); (j) is the wear track depth profile curve of the coating in Comparative Example 3 (D3); (k) is the wear track depth profile curve of the coating in Comparative Example 4 (D4); (l) is the wear track cross-sectional depth profile curve of the coating in Example 2 (S2); Figure 5 The images show the SEM morphology and EDS elemental distribution of the wear trajectories of the coatings in each embodiment and comparative example; among them, (a) SEM morphology and EDS elemental distribution of the wear trajectory of the coating in Comparative Example 1 (D1); (b) SEM morphology and EDS elemental distribution of the wear trajectory of the coating in Comparative Example 2 (D2); (c) is the SEM morphology and EDS elemental distribution diagram of the wear trajectory of the coating in Example 1 (S1); (d) shows the SEM morphology and EDS elemental distribution of the wear trajectory of the coating in Comparative Example 3 (D3); (e) shows the SEM morphology and EDS elemental distribution of the wear trajectory of the coating in Comparative Example 4 (D4); (f) shows the SEM morphology and EDS elemental distribution of the coating wear trajectory in Example 2 (S2); Figure 6 The images show the SEM morphology and EDS elemental distribution of the coating cross-sections in each embodiment and comparative example; where, (a) SEM morphology and EDS element distribution of the coating cross section of Comparative Example 1 (D1); (b) shows the SEM morphology and EDS elemental distribution of the coating cross section in Comparative Example 2 (D2); (c) is the SEM morphology and EDS elemental distribution diagram of the coating cross section of Example 1 (S1); (d) shows the SEM morphology and EDS elemental distribution of the coating cross section of Comparative Example 3 (D3); (e) shows the SEM morphology and EDS elemental distribution of the coating cross section of Comparative Example 4 (D4); (f) shows the SEM morphology and EDS elemental distribution of the coating cross section in Example 2 (S2); Figure 7The images show Raman and XPS analysis of the worn area of the coating in Example 2 (S2); where, (a) is the Raman spectrum of the coating in Example 2 (S2) before wear; (b) is the Raman spectrum of the wear area of the coating in Example 2 (S2); (c) is the C 1s spectrum of the worn area of the coating in Example 2 (S2); (d) is the S2p spectrum of the wear region of the coating in Example 2 (S2); (e) is the Mo 3d spectrum of the worn area of the coating in Example 2 (S2); (f) is the O 1s spectrum of the worn area of the coating in Example 2 (S2); Figure 8 This is a schematic diagram of the tribological mechanism of the MoS2 / C alternating stacked composite coating of the present invention. Detailed Implementation
[0024] The technical solutions (including preferred technical solutions) of the present invention will be further described in detail below with reference to the accompanying drawings and by way of listing some optional embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0025] Example 1 like Figure 1 As shown, this embodiment provides a composite coating (denoted as S1) prepared by sequentially stacking a carbon layer and a molybdenum disulfide layer on a Si substrate using magnetron sputtering technology. The preparation steps are as follows: 1. Substrate pretreatment: The Si(100) substrate was ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each, dried in an 80 ℃ oven and then sent into the magnetron sputtering chamber with the substrate temperature set to 180 ℃.
[0026] 2. Coating deposition: Under an argon atmosphere with a gas flow rate of 20 sccm and a gas pressure of 1.0 Pa, a pure graphite target is sputtered using a DC power supply with a power of 120 W and a bias voltage of 80 V. After a deposition time of 45 min, the deposition is paused for 2 min and then continued for another 45 min. The total deposition time is 90 min, which forms the first carbon layer on the Si substrate. The MoS2 target was sputtered using an RF power supply at 80 W. After a 45-minute deposition period, the deposition was paused for 2 minutes and continued for another 45 minutes, for a total deposition time of 90 minutes. This resulted in the formation of the first molybdenum disulfide layer on the first carbon layer.
[0027] 3. After deposition, cool to room temperature in an argon atmosphere and store in a desiccator.
[0028] Cross-sectional SEM observations showed that the total thickness of the S1 coating was 0.68 μm, of which the carbon layer was 0.27 μm thick and the molybdenum disulfide layer was 0.41 μm thick.
[0029] Example 2 This embodiment provides a composite coating (denoted as S2) prepared by sequentially stacking a carbon layer, a molybdenum disulfide layer, another carbon layer, and another molybdenum disulfide layer on a Si substrate using magnetron sputtering technology. The preparation steps are as follows: 1. Substrate pretreatment: The Si(100) substrate was ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each, dried in an 80 ℃ oven and then sent into the magnetron sputtering chamber with the substrate temperature set to 180 ℃.
[0030] 2. Coating deposition: Under an argon atmosphere with a gas flow rate of 20 sccm and a gas pressure of 1.0 Pa, a pure graphite target is sputtered using a DC power supply with a power of 120 W and a bias voltage of 80 V. The deposition time is 45 min, which forms the first carbon layer on the Si substrate. Then, the MoS2 target is sputtered with an RF power supply at a power of 80 W for a deposition time of 45 min, thus forming the first molybdenum disulfide layer on the first carbon layer. Following the above procedure, sputter pure graphite and MoS2 targets again, with a total deposition time of 180 min.
[0031] 3. After deposition, cool to room temperature in an argon atmosphere and store in a desiccator.
[0032] Cross-sectional SEM observations showed that the total thickness of the S2 coating was 0.72 μm, with each carbon layer being 0.15 μm thick and each molybdenum disulfide layer being 0.21 μm thick.
[0033] Comparative Example 1 This embodiment provides a method for depositing a MoS2 coating (denoted as D1) on a Si substrate using magnetron sputtering technology. The preparation steps are as follows: 1. Substrate pretreatment: The Si(100) substrate was ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each, dried in an 80 ℃ oven and then sent into the magnetron sputtering chamber with the substrate temperature set to 180 ℃.
[0034] 2. Coating deposition: Under an argon atmosphere with a gas flow rate of 20 sccm and a gas pressure of 1.0 Pa, the MoS2 target was sputtered using an RF power supply with a power of 80 W. After every 45 min of deposition time, the process was paused for 2 min until the deposition time reached 180 min.
[0035] 3. After deposition, cool to room temperature in an argon atmosphere and store in a desiccator.
[0036] Cross-sectional SEM observations showed that the total thickness of the D1 coating was 0.81 μm.
[0037] Comparative Example 2 This embodiment provides a method for depositing a graphite coating (denoted as D2) on a Si substrate using magnetron sputtering technology. The preparation steps are as follows: 1. Substrate pretreatment: The Si(100) substrate was ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each, dried in an 80 ℃ oven and then sent into the magnetron sputtering chamber with the substrate temperature set to 180 ℃.
[0038] 2. Coating deposition: Under an argon atmosphere with a gas flow rate of 20 sccm and a gas pressure of 1.0 Pa, a pure graphite target was sputtered using a DC power supply with a power of 120 W and a bias voltage of 80 V. After every 45 min of deposition time, the process was paused for 2 min until the deposition time reached 180 min.
[0039] 3. After deposition, cool to room temperature in an argon atmosphere and store in a desiccator.
[0040] Cross-sectional SEM observations showed that the total thickness of the D2 coating was 0.54 μm.
[0041] Comparative Example 3 This embodiment provides a composite coating (denoted as D3) prepared by sequentially stacking a molybdenum disulfide layer and a carbon layer on a Si substrate using magnetron sputtering technology. The preparation steps are as follows: 1. Substrate pretreatment: The Si(100) substrate was ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each, dried in an 80 ℃ oven and then sent into the magnetron sputtering chamber with the substrate temperature set to 180 ℃.
[0042] 2. Coating deposition: Under an argon atmosphere with a gas flow rate of 20 sccm and a gas pressure of 1.0 Pa, the MoS2 target was sputtered using an RF power supply at a power of 80 W. After a deposition time of 45 min, the deposition was paused for 2 min and continued for another 45 min, with a total deposition time of 90 min, thus forming the first molybdenum disulfide layer on the Si substrate. Then, a pure graphite target was sputtered using a DC power supply at a power of 120 W and a bias voltage of 80 V. After a deposition time of 45 min, the deposition was paused for 2 min and continued for another 45 min, for a total deposition time of 90 min. This resulted in the formation of the first carbon layer in the first molybdenum disulfide layer.
[0043] 3. After deposition, cool to room temperature in an argon atmosphere and store in a desiccator.
[0044] Cross-sectional SEM observations showed that the total thickness of the D3 coating was 0.68 μm, with each carbon layer being 0.27 μm thick and each molybdenum disulfide layer being 0.41 μm thick.
[0045] Comparative Example 4 This embodiment provides a composite coating (denoted as D4) prepared by sequentially stacking a molybdenum disulfide layer, a carbon layer, another molybdenum disulfide layer, and another carbon layer on a Si substrate using magnetron sputtering technology. The preparation steps are as follows: 1. Substrate pretreatment: The Si(100) substrate was ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each, dried in an 80 ℃ oven and then sent into the magnetron sputtering chamber with the substrate temperature set to 180 ℃.
[0046] 2. Coating deposition: Under an argon atmosphere with a gas flow rate of 20 sccm and a gas pressure of 1.0 Pa, the MoS2 target was sputtered using an RF power supply at a power of 80 W for a deposition time of 45 min, thus forming the first molybdenum disulfide layer on the Si substrate. Then, a pure graphite target was sputtered using a DC power supply at a power of 120 W and a bias voltage of 80 V for a deposition time of 45 min, which formed the first carbon layer in the first molybdenum disulfide layer. Following the above procedure, the MoS2 target and the pure graphite target were sputtered again, with a total deposition time of 180 min.
[0047] 3. After deposition, cool to room temperature in an argon atmosphere and store in a desiccator.
[0048] Cross-sectional SEM observations showed that the total thickness of the D4 coating was 0.72 μm, with each carbon layer being 0.15 μm thick and each molybdenum disulfide layer being 0.21 μm thick.
[0049] I. Friction Performance Test like Figure 2 As shown, the friction properties of the coatings prepared in each embodiment and comparative example were tested using a ball-disc friction testing machine (TriboStudio). The test process and parameter settings are as follows: The mating component used was a GCr15 steel ball with a diameter of Φ5 mm, a hardness of HRC 62, and a surface roughness Ra of 0.03-0.06 μm. A load of 0.5 N was applied, the testing machine speed was 20 rpm, corresponding to a linear velocity of approximately 0.0042 m / s, and the sliding radius was set to 4 mm. The testing environment was controlled at room temperature of 25±1℃ and relative humidity of 45±5%. Each sample was tested in triplicate, and the average value was taken as the final test result. The results are as follows: Figure 3 As shown in Table 1.
[0050] Table 1. Friction coefficients measured in each embodiment and comparative example. The coefficient of friction is the time-averaged shear resistance at the contact interface throughout the entire test process, reflecting the overall lubrication effect during the sliding process. Generally speaking, for composite coatings containing carbon and MoS2 layers, with the same alternating stacking order, the coefficient of friction measured for a four-layer structure is generally lower than that for a two-layer structure. Furthermore, with the same number of coating layers, the coefficient of friction measured for a composite coating with the carbon layer as the innermost layer in contact with the substrate and the MoS2 layer as the outermost layer is generally lower than that for a composite coating with the MoS2 layer as the innermost layer in contact with the substrate and the carbon layer as the outermost layer.
[0051] II. Morphology of the Wear Zone and Analysis of Wear Track Cross-Section Depth Profile To analyze the reasons for the differences between the friction systems of the various embodiments and comparative examples, the wear morphology of the coating was first observed. The wear morphology reflects whether the coating has suffered structural damage such as peeling or exposure of the underlying layer in the later stages of friction.
[0052] Depend on Figure 4 Images (a) and (g) show that the wear zone of the MoS2 monolayer (D1) is extremely rough, exhibiting deep grooves, coating peeling, and fragmentation. Figure 4 (b) and (h) show that the wear area of the C monolayer (D2) has a narrower wear mark and a relatively smooth surface.
[0053] Depend on Figure 4 As shown in (c), (d), (i), and (j), the wear-scarred area of S1 shows obvious peeling, exposing the underlying layer. The wear-scarred area of D3, which is in the opposite stacking order of S1, is relatively flat, but still shows partial peeling. This is because the outer layer of MoS2 in S1 is worn through, causing interface instability, while the top layer C of D3 bears the load and protects the underlying MoS2 layer from direct damage.
[0054] The above phenomena indicate that MoS2 undergoes rapid delamination and abrasive wear during friction, while C undergoes slight abrasive wear. This wear resistance is determined by the material's structural density and hardness.
[0055] And by Figure 4 (e), (f), (k), and (l) show that, with almost the same total coating thickness, the flatness of the wear area provided by the four-layer structure coating of S2 and D4 is better than that of the two-layer structure coating of S1 and D2. This indicates that the multi-layer interface itself helps to suppress local stress concentration and spalling, making the wear process more uniform. The increase in the number of stacking alternations has an effect on resisting spalling and stabilizing the friction surface.
[0056] Further comparison of S2 and D4, both four-layer coatings, revealed that the wear-marked area of S2 was smoother and flatter than that of D4, while D4 exhibited peeling. However, the wear-marked depth of S2 was greater than that of D4. This indicates that MoS2, as the soft top layer, was consumed during friction, while C, as the hard top layer, had strong wear resistance and retained more of the original coating. The structural difference in the top layer materials again influenced the wear depth. However, because the initial C layer of S2 had strong adhesion to the substrate, it did not peel off even at greater depths. In contrast, the initial MoS2 layer of D4 had relatively weak adhesion to the film substrate, resulting in peeling and a shallower but less smooth surface. This suggests that the bottom layer material primarily affects the stability of the coating surface smoothness.
[0057] III. SEM morphology and EDS elemental distribution of wear tracks The comparison of wear behaviors between S2 and D4 above shows that there is no simple monotonic relationship between the surface smoothness of the worn surface and the depth of the wear track. To further explore the coating lubrication mechanism, the morphology of the friction areas in each embodiment and comparative example was observed by SEM microscopic characterization: Depend on Figure 5 As shown in (a)~(f), the D1 wear track shows obvious deep grooves, large-area peeling and debris, indicating severe delamination and abrasive wear. Combined with EDS characterization analysis, the Si signal increased significantly after D1 wear, indicating that the coating had been worn through to the substrate, with a large loss of Mo and S elements, accompanied by obvious oxidation and failure of the lubricating phase.
[0058] D2 only showed slight scratches and no peeling. This is because the hard C layer only experienced slight abrasive wear. Combined with EDS characterization analysis, the C element content in the wear marks was high, and the Mo and S signals were extremely weak. Only the hard carbon film was worn, and there was no lubricating phase replenishment.
[0059] S1 peeled off, the top layer of MoS2 was worn through and the bottom C layer was exposed, and the interface was unstable and peeled off. Combined with EDS characterization analysis, the Si signal was prominent after wear, the Mo and S contents decreased, and the C signal was relatively enhanced, confirming that the surface MoS2 was worn through and the bottom C and silicon substrate were exposed.
[0060] D3 is relatively flat, and a localized transfer lubricating film is visible. The C layer is on the outer layer, and the MoS2 layer forms the lubricating film underneath. Combined with EDS characterization analysis, C, Mo, and S elements coexist uniformly in the wear track, indicating the formation of a stable mixed lubricating film. However, the O signal is strong, indicating that when MoS2 comes into contact with the substrate Si, the crystal voids in its columnar crystal structure provide diffusion channels for oxygen, causing MoS2 to be easily partially oxidized during friction, thus leading to a decrease in the lubrication efficiency of the mixed film.
[0061] D4 is generally flat with only slight peeling. Combined with EDS characterization analysis, the C content in the D4 wear track is relatively high, and the distribution of Mo and S is relatively uniform. However, because the outermost layer is a C layer, the output of the lubricating phase is limited.
[0062] The S2 wear track surface is intact and smooth, completely covered by a continuous and uniform lubricating film, without cracks, peeling, or furrows, exhibiting only slight lamellar wear. Mo, S, and C are uniformly distributed within the wear track with appropriate content, and no substrate signal is exposed, indicating the formation of a continuous, self-supplied MoS2 / C composite lubricating film. The lubricating phase is durable and stable, and the film layer has not experienced penetration failure. Its O signal is weaker than that of D3 and D4 (where MoS2 is in contact with the substrate), because the multilayer structure of S2 effectively inhibits oxygen diffusion into the interior, while MoS2 oriented and rapidly forms a protective film during friction, preventing further oxidation.
[0063] The above phenomena indicate that neither a single C layer nor a single MoS2 layer (D1 and D2) can simultaneously meet the requirements of coating stability and lubricity. For the two-layer structure (D3 and S1), the synergistic effect of MoS2 and C can form a transfer lubrication film, significantly improving film integrity.
[0064] The four-layer alternating structure (D4 and S2) effectively inhibits crack propagation and delays film wear-through through multiple interface effects, exhibiting optimal film integrity, lubricant phase retention, and failure resistance in micro-wear. The performance advantages of both depend on the arrangement of the initiating layer and the surface layer, specifically: The smoothness and peeling of the coating surface reflect the uniformity and stability of the wear process. Even if the wear track is deep, as long as the surface is smooth, there is no peeling, and the elements are uniformly covered, it means that the coating has formed a stable lubricating film during the friction process and no sudden failure has occurred. That is, the uniform coexistence of Mo, S, and C is a necessary condition for the formation of a stable lubricating film, rather than simply relying on the thickness of the original coating.
[0065] The top layer of D4 is hard C, which has strong wear resistance, resulting in a small wear track depth. However, since the initial layer is MoS2, the film-substrate bonding is relatively weak. Slight peeling occurs during the friction process, and the EDS shows that the C signal is high and the Mo / S output is limited, indicating that the lubricating phase has not fully participated in the surface coverage. As a result, the surface smoothness is good but not optimal.
[0066] The top layer of S2 is soft MoS2, which is consumed during friction, resulting in thinning of the original coating and thus a larger wear track depth. However, the initial C layer is firmly bonded to the substrate, and the multi-layer structure effectively inhibits the growth of columnar crystals, allowing MoS2 and C to fully mix and reconstruct at the interface, forming a continuous and uniform composite lubricating film, ultimately achieving the smoothest surface, no peeling, and uniform coexistence of elements.
[0067] The design of the four-layer alternating structure should follow the principle of: using C as the bottom layer to ensure bonding and anti-stripping, and using MoS2 as the top layer to provide lubrication and self-renewal capability, achieving synergy between the two through multi-layer interfaces.
[0068] IV. SEM morphology and EDS elemental distribution of the complete coating cross section To reveal the fundamental reasons for the differences in wear track morphology and tribological properties from the perspective of the internal microstructure of the coating, the cross-sectional morphology of the coatings in each embodiment and comparative example was characterized by SEM.
[0069] like Figure 6 As shown in (a) to (f), the cross-section of coating D1 exhibits a typical coarse columnar crystal structure with poor density and low mechanical strength. It is highly susceptible to peeling and wear-through during friction, which is the core structural reason for its severe wear. Coating D2 has a uniform amorphous carbon structure with a dense and uniform coating, possessing excellent load-bearing and deformation resistance. However, due to the absence of a lubricating phase, it cannot achieve ultra-low friction. Coatings S1 and D3 have clear interfaces with slight columnar characteristics. Although the overall density of the coating is improved, the interfacial bonding stability is insufficient, and the structural defects caused by the columnar crystals of the MoS2 layer are not eliminated. Coatings D4 and S2 exhibit a multi-layered, alternating, dense structure with straight interfaces, indicating that layer C blocks the vertical continuous growth of the columnar crystals in the MoS2 layer, thus eliminating the problem of porous coating defects at its source.
[0070] Combination Figure 6 Cross-sectional morphology analysis reveals that the internal microstructure of the coating determines its macroscopic tribological properties. First, the structural density directly determines the coating's resistance to spalling and its load-bearing stability. The coarse columnar crystal structure of the D1 (MoS2 layer) is loose and porous, with the inter-column interfaces becoming natural channels for crack initiation and propagation. Under shear stress, columnar crystal peeling is highly likely to occur, leading to rapid loss of the lubricating phase and large-area wear.
[0071] In contrast, the amorphous carbon structure of D2 (C layer) is boundary-free, dense, and uniform. Although it lacks a lubricating phase, it possesses excellent resistance to plastic deformation, thus exhibiting only slight abrasive wear. Secondly, the introduction of the C layer effectively blocks the vertical continuous growth of MoS2 columnar crystals and improves the coating density: the elimination of columnar crystals means a significant reduction in internal defects (porosity, penetrating grain boundaries) in the coating, and a significant improvement in resistance to crack propagation. This is the microstructure root of why the four-layer structure can maintain high surface integrity even after wear.
[0072] Finally, the material of the initiating layer determines the quality of the film-substrate bonding, thus affecting the entire coating system: both S2 and D4 are four-layered, densely alternating structures, but S2 uses a C layer that directly contacts the Si substrate, allowing for strong chemical bonding and good lattice matching between C and Si, resulting in a firmly anchored substrate. In contrast, D4 uses MoS2 as the initiating layer, where the interfacial bonding between MoS2 and Si is weaker (mainly relying on van der Waals forces). This difference is directly reflected in… Figure 4Regarding the spalling behavior: S2 showed no spalling even with a large wear track depth; D4, although shallow, showed slight spalling points. This demonstrates that the dense, multi-layered internal structure endows the coating with superior resistance to crack propagation, while the initial C layer provides a highly reliable mechanical anchor for the entire system. Together, they determine the structural stability during macroscopic wear.
[0073] V. Raman and XPS analysis of the wear zone of the coating To further elucidate the formation mechanism and composition of the lubricating film from the perspective of interfacial chemical bond states and phase composition, and to investigate whether element migration, oxidation, graphitization, or other issues occurred during the friction process, X-ray photoelectron spectroscopy (XPS) and laser Raman spectroscopy were used to characterize the wear-marked region of S2. The results are as follows: Figure 7 As shown.
[0074] Figure 7 (a) The D and G peaks of the original carbon coating of S2 are broad and weak characteristic peaks, indicating an amorphous structure, while the moderate-intensity characteristic peak of MoS2 (E) is also present. 1 2g~382 cm -1 A1g~408 cm -1 This reflects the crystal structure of the deposited state. The central region of the worn coating ( Figure 7 b) Significant changes were observed: the carbon-related D and G peaks showed markedly increased intensity and clearer peak shapes, while the I(D) / I(G) ratio decreased from approximately 1.2 before wear to approximately 0.8 after wear, indicating that the amorphous carbon underwent partial graphitization. Meanwhile, the MoS2-related E... 1 The 2g and A1g peaks became sharper, indicating that the MoS2 sheets underwent a preferred orientation, with their basal planes aligned parallel to the sliding direction.
[0075] The driving force behind this orientation rearrangement originates from the high contact shear stress at the sliding interface. Under shear stress, the low-shear-strength basal planes of MoS2 rotate and align parallel to the shear direction, which is energy-advantageous, simultaneously reducing surface energy and sliding resistance. This mechanochemical orientation rearrangement process, in conjunction with friction-induced graphitization of the carbon phase, contributes to the excellent lubrication properties exhibited by the S2 friction film.
[0076] X-ray photoelectron spectroscopy (XPS) analysis further confirmed the evolution of the chemical state of elements within the wear-marked region. For example... Figure 7 As shown in (c)~(d), the C 1s spectrum of S2 shows sp 2 The area ratio of the carbon peak is significantly higher than that of the sp peak. 3The presence of carbon peaks indicates significant friction-induced graphitization of the coating during friction, consistent with partial graphitization observed in Raman spectroscopy. For the Mo3d and S2p spectra, the characteristic peaks of MoS2 still dominate in the wear region, indicating that the lubricating sulfide phase is well preserved during friction. Notably, no significant MoO3 formation was detected, suggesting that the multilayer structure effectively suppressed the oxidation of MoS2 during sliding. The coexistence of graphitized carbon and the stable MoS2 phase in the friction film provides the chemical basis for the sustained low-friction behavior of the S2 coating.
[0077] Combined Raman and XPS analyses revealed two key chemical changes in S2 during the friction process: the transformation of amorphous carbon into graphitized carbon and the directional alignment of MoS2 sheets along the sliding direction. The former reduces the shear resistance of the carbon phase, while the latter orients the easy-slip basal planes of MoS2 towards the shear direction. Together, these two changes form a composite lubricating film that possesses both low frictional properties and oxidation resistance.
[0078] More importantly, the formation of the lubricating film does not depend on the passive consumption of the original coating, but on the active chemical reconstruction under the shear mixing of multiple interfacial layers. The C layer blocks the growth of MoS2 columnar crystals, allowing the two to mix uniformly at the nanoscale; frictional stress induces carbon graphitization and MoS2 orientation rearrangement, ultimately generating an adaptive surface film.
[0079] In contrast, D4 (C top layer, MoS2 initiation) has a multi-layered structure, but the top layer of C hinders the migration of MoS2 to the surface, and the interfacial bonding is weak, preventing sufficient graphitization and orientation reconstruction. Therefore, its surface coating is mainly C, limiting its lubrication effect. This further confirms that a multi-layered dense structure alone is insufficient to achieve ultra-low friction; the key lies in the arrangement of a top layer of MoS2 and an initiation layer of C, which provides a material channel for friction-induced chemical reconstruction.
[0080] In summary, the complete process of gradually building a stable lubrication system in the multilayer composite coating (C / MoS2 / C / MoS2) of Example 2 (S2) during friction and sliding is as follows: Figure 8 As shown. In the initial contact stage of friction, relying on the smooth coating surface and the layered structure of the top layer MoS2, low-resistance and stable contact and initiation are achieved. As friction continues, the hard carbon layer effectively bears the external load and reasonably disperses the interfacial stress. The carbon layer bears the load, and the MoS2 layer bears the shear deformation, thus achieving a reasonable distribution of stress. Under the action of frictional shear, the interface undergoes friction-induced graphitization transformation, and at the same time, the MoS2 sheets are oriented along the sliding direction, gradually generating a uniform and continuous composite lubricating film. After entering the stable sliding stage, the C-MoS2 composite lubricating film completely covers the friction contact area, isolating the coating from direct hard contact with the mating pair, and ultimately ensuring that the coating maintains a low-friction and highly stable sliding service state for a long time.
[0081] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Those skilled in the art can readily implement the present invention based on the accompanying drawings and the above description. However, any modifications, alterations, or variations made by those skilled in the art without departing from the scope of the present invention, utilizing the disclosed technical content, are equivalent embodiments of the present invention. Furthermore, any modifications, alterations, or variations made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the present invention.
Claims
1. A C / MoS2 alternating stacked composite coating with excellent tribological properties, characterized in that, The composite coating is attached to the surface of the substrate. The composite coating is formed by alternating stacking of carbon layers and molybdenum disulfide layers. The innermost layer of the composite coating is a carbon layer that is in contact with the substrate, and the outermost layer is a molybdenum disulfide layer. Both the carbon layer and the molybdenum disulfide layer are at least one layer. The thickness of each carbon layer is 0.08~0.30 μm, and the thickness of each molybdenum disulfide layer is 0.12~0.45 μm. The total thickness of the composite coating is 0.56~0.8 μm.
2. The composite coating according to claim 1, characterized in that, When both the carbon layer and the molybdenum disulfide layer are single layers, the thickness of the carbon layer is 0.2~0.3 μm, and the thickness of the molybdenum disulfide layer is 0.36~0.45 μm.
3. The composite coating according to claim 1, characterized in that, When both the carbon layer and the molybdenum disulfide layer are two layers, the thickness of each carbon layer is 0.12~0.18 μm, and the thickness of each molybdenum disulfide layer is 0.17~0.22 μm.
4. The composite coating according to claim 1, characterized in that, When both the carbon layer and the molybdenum disulfide layer are three layers, the thickness of each carbon layer is 0.08~0.1 μm, and the thickness of each molybdenum disulfide layer is 0.12~0.14 μm.
5. The composite coating according to claim 3, characterized in that, When both the carbon layer and the molybdenum disulfide layer are two layers, the thickness of each carbon layer is 0.15 μm and the thickness of each molybdenum disulfide layer is 0.21 μm.
6. A method for preparing a C / MoS2 alternating stacked composite coating with excellent tribological properties according to any one of claims 1 to 5, characterized in that, Includes the following steps: Step 1) After cleaning and drying the substrate, place it in the magnetron sputtering chamber and set the substrate temperature; Step 2) Under a protective atmosphere, according to the preset stacking cycle, number of stacked layers and design thickness of each single layer of the composite coating, set the deposition time of each layer by magnetron sputtering, and use graphite target and molybdenum disulfide target alternately for sputtering deposition. First, deposit a carbon layer on the substrate, and then deposit a molybdenum disulfide layer on the carbon layer. Repeat this alternating deposition cycle until the preset number of stacked layers of the composite coating is reached. Step 3) After deposition, cool to room temperature to obtain a C / MoS2 alternating stacked composite coating deposited on the substrate.
7. The method according to claim 6, characterized in that, In step 1), the base temperature is set to 180 ℃.
8. The method according to claim 6, characterized in that, In step 2), the protective gas is argon, the gas flow rate is 20 sccm, and the gas pressure is 1.0 Pa.
9. The method according to claim 6, characterized in that, In step 2), the carbon layer is deposited using DC magnetron sputtering mode with a sputtering power of 120 W, a substrate bias of 80 V, and a total deposition time of 90 min for each carbon layer; the molybdenum disulfide layer is deposited using radio frequency magnetron sputtering mode with a sputtering power of 80 W and a total deposition time of 90 min for each molybdenum disulfide layer.
10. The application of the C / MoS2 alternating stacked composite coating with excellent tribological properties as described in any one of claims 1 to 5 in friction reduction and protection of the surface of key moving parts of precision instruments.
Citation Information
Patent Citations
A low-orbit space radiation resistant self-adapting molybdenum disulfide-based multilayer composite film and a preparation method thereof
CN119243098B